2018
DOI: 10.3748/wjg.v24.i43.4846
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer: A review of clinical diagnosis, epidemiology, treatment and outcomes

Abstract: This review aims to outline the most up-to-date knowledge of pancreatic adenocarcinoma risk, diagnostics, treatment and outcomes, while identifying gaps that aim to stimulate further research in this understudied malignancy. Pancreatic adenocarcinoma is a lethal condition with a rising incidence, predicted to become the second leading cause of cancer death in some regions. It often presents at an advanced stage, which contributes to poor five-year survival rates of 2%-9%, ranking firmly last amongst all cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
1,150
0
53

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,356 publications
(1,218 citation statements)
references
References 110 publications
15
1,150
0
53
Order By: Relevance
“…Ninety percentage of pancreatic tumors are pancreatic ductal adenocarcinoma (PDAC) while 3-5% are neuroendocrine tumors (PNETs) (191). Smoking, heavy alcohol consumption, obesity, H. pylori infection, and chronic pancreatitis are risk factors (192). Prognosis is incredibly poor, approximately 70% of patients will succumb to the disease in the first year (193).…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Ninety percentage of pancreatic tumors are pancreatic ductal adenocarcinoma (PDAC) while 3-5% are neuroendocrine tumors (PNETs) (191). Smoking, heavy alcohol consumption, obesity, H. pylori infection, and chronic pancreatitis are risk factors (192). Prognosis is incredibly poor, approximately 70% of patients will succumb to the disease in the first year (193).…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…The "good" quality studies on salivary biomarkers and lung cancer are those demonstrating an association with EGFR, the 5 mRNA, microbiota and cytokines (8)(9)(10)(11) (45). Similarly, pancreatic carcinoma is insidious, very aggressive and in most cases diagnosed at a very late stage, being associated to a very poor prognosis (46). With regard to gastric cancer 7 studies were included in the present review (15)(16)(17)25,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether PPT might enhance Gem-mediated cytotoxicity and determine if the combined effect is synergistic, additive or antagonistic, we measured cell viability by treating with 9 increasing doses of the combination of Gem and PPT at fixed ratios (1:1 in L3.6 cells and 37.5:1 in MIA PaCa-2 and KPC cells, based on their IC50 values of Gem and PPT, according to established protocols26). We found that K17-expressing cells had significantly lower cell viability under the same doses compared with non-K17-expressing cells ( Fig.…”
Section: Targeting Microtubule Disassembly Rather Than Microtubule Asmentioning
confidence: 99%